Sikap Kristen Terhadap Ujaran Kebencian di Media Sosial Berdasarkan Lukas 6:27-36 - Hananti, Vasika; Nduru, Parminta (Sekolah Tinggi Teologi Sriwijaya, 2025)
In the realm of social media, hate speech based on religion is a possible and concerning phenomenon. Such hate speech causes unrest among individuals or groups who feel victimized. Several theologians have responded to the issue of hate speech from the perspective of Christian Religious Education and ecclesiastical encyclicals. However, so far, no one has addressed it from a biblical perspective. Therefore, this paper seeks to examine Luke 6:27–36 to understand how Christians should respond to hate speech. To interpret Luke 6:27–36, the author employs a socio-redactional analysis. The results of this study indicate that Luke 6:27-36 contains a message that hate speech should not be responded to with hate speech, but with love that is manifested in good deeds, blessings, prayers, being generous, and acting as Christians want to others to do to Christians. Thus, the theological message of Luke 6:27-30 can be a theological reflection that can be applied by Christians today in responding to the rise of hate speech on the basis of religion in Indonesia thourgh social media.